MODERN BORROWINGS IN THE RUSSIAN LANGUAGE (Spectrum Journal of Innovation, Reforms and Development, 2025)
The article is devoted to the study of modern borrowings in the Russian language, as well as their influence on its structure and development. The main sources of borrowings, such as English, French, German and other languages, as well as ways of adapting borrowed words in the Russian language are considered. The article also analyzes the role of borrowings in modern communication, their perception by native speakers and their impact on language culture.